Bias, Power, and Epistemic Authority in the Dewey Decimal Classification System (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The Dewey Decimal Classification (DDC) system is critically reviewed in this paper using the intersecting perspectives of bias, power, and epistemic authority. Although DDC has traditionally been one of the most popular and useful knowledge-organizing tools, it was shaped by the philosophical, cultural, and historical beliefs of its designers - most especially, Western, Christian, and Enlightenment epistemologies. This study identifies the presence of hierarchical, Eurocentric, and gendered biases in the system that determines the visibility and legitimacy of various knowledge traditions through an analysis of its foundations in the works of Bacon, Harris, and Dewey. The paper also examines the manner in which power is exercised in classification choices affecting user experience as well as power to determine what is deemed as knowledge. The paper with the help of epistemic stance puts forward a greater understanding of the ideological forces behind DDC and the necessity of an inclusive, pluralistic, and context-specific reforms. In conclusion, the analysis can be used in the current discussions of how to develop equitable knowledge-organization systems that are reflected by the diversity and complexity of global epistemologies.